Parents' Experiences Navigating Intervention Systems for Young Children With Mild Language Delays. (September 2017) - Marshall, Jennifer; Adelman, Andrea; Kesten, Stacey M.; Natale, Ruby A.; Elbaum, Batya
The purpose of this study was to explore the experiences of parents of children with mild language delays who were referred to an Individuals With Disabilities Education Act (IDEA) birth-to-3 or preschool program, were determined not eligible for services, and were referred on to a community-based program for short-term speech-language therapy. Interviews were conducted in the parents' preferred language (10 Spanish, 10 English). A grounded theory approach was applied to identify emergent themes. Results indicated that the process of recognizing a developmental delay, receiving assessment results, and enrolling in services presents challenges that require parents to demonstrate engagement and advocacy throughout. This study highlights parents' motivations for seeking out early intervention services and underscores the importance of understanding parents' experiences navigating developmental service systems. Program planners can partner with parents to address barriers and also capitalize on successes to facilitate timely response to developmental concerns, appropriate referrals, and effective interventions.